DOMINANT FACTOR OF RISING URIC ACID LEVELS IN ARTHTRITIS AT WORKING AREA OF PUBLIC HEALTH IN JEMBER - Handayani, Luh Titi (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2017)
Abstract: Joint pain or commonly called arthritis is disease which it often found. Arthritis is a group of heterogeneous disease as that caused by deposition of monosodium urate crystals (MSU) in tissue or because of uric acid super saturation in the extracellular fluid as the most important thing of arthritis inflammation. Arthritis is an inflammation disorder which unknown cause that commonly affects synovial joints. The purpose of this research was to analyze dominant factor associated with dietary habit variables, blood urea nitrogen (BUN), and body mass index (BMI) on uric acid level in arthritis at working area of public health in Jember regency. The method of this research was correlational with cross sectional design. The technique to take the sample was purposive sample with 31 samples. Questionnaire and observation checklist used to collect the data. The research result based on the logistic regression test with 95% (ɑ ≤ 0.05) was achieved the value of p= 0.038, it means that totally dietary habit variable, BMI, and BUN levels influenced uric acid levels by seeing the value of R square that all three predictor variables influenced uric acid levels approximately 32. The accuracy of prediction variable at three independent variables on the value of uric acid levels was 67.7%. Through bivariate test showed that predictor variables which significantly has correlation on uric acid levels was BMI with significant value 0.026.Conclusion: overall it was achieved that the variable of dietary habit, BMI, and BUN levels influenced uric acid levels and the most correlated on uric acid levels was BMI. Suggestion: implementing low purine diet, enough exercises and periodically checks the function of kidney excretion, especially in a risk group. Keywords: Dominant Factor, Uric Acid, Arthritis